Metastasis of Drosophila tumors - Shearn, Allen (Henry Stewart Talks, 2008)
Recessive lethal mutations of Drosophila cause brain tumors that are metastatic, Despite their apparent similarities, tumors caused by different mutations have different metastatic properties, The metastasis of tumors caused by lgl mutations is enhanced by secretion of MMP1 from the tumor cells themselves, The metastasis of tumors caused by brat mutations is not enhanced by secretion of MMP1 from the tumor cells themselves, but is enhanced by MMP1 that host cells are induced to secrete
Reviewed at 2017/09/25